ESMO recommendations on the standard methods to detect RET fusions and mutations in daily practice and clinical research - Belli, Carmen; Penault-Llorca, F.; Ladanyi, M.; Normanno, N.; Scoazec, J. -Y.; Lacroix, L.; Reis-Filho, J. S.; Subbiah, V.; Gainor, J. F.; Endris, Volker; Repetto, M.; Drilon, A.; et al. (Annals of oncology, 2021)
Aberrant activation of RET is a critical driver of growth and proliferation in diverse solid tumours. Multikinase inhibitors (MKIs) showing anti-RET activities have been tested in RET-altered tumours with variable results. The low target specificity with consequent increase in side-effects and off-target toxicities resulting in dose reduction and drug discontinuation are some of the major issues with MKIs. To overcome these issues, new selective RET inhibitors such as pralsetinib (BLU-667) and selpercatinib (LOXO-292) have been developed in clinical trials, with selpercatinib recently approved by the Food and Drug Administration (FDA). The results of these trials showed marked and durable antitumour activity and manageable toxicity profiles in patients with RET-altered tumours. The European Society for Medical Oncology (ESMO) Translational Research and Precision Medicine Working Group (TR and PM WG) launched a collaborative project to review the available methods for the detection of RET gene alterations, their potential applications and strategies for the implementation of a rational approach for the detection of RET fusion genes and mutations in human malignancies. We present here recommendations for the routine clinical detection of targetable RET rearrangements and mutations.
Gesehen am 30.04.2021